Responses of Phytoplankton Communities to Flow Regulation in Northeastern Riverine Wetlands of China - Yao Meng; Haitao Wu (Diversity, 2023)
Among the impacts of dam construction on river ecosystem, runoff regulation and habitat fragmentation are the two major concerns. Herein, the response characteristics of phytoplankton communities to reservoir impoundment and dam interception were explored by taking Manjiang and Songjiang rivers, where a man-made engineering project was constructed, and the natural stretches located in the up-streams as the research objects. The results obtained revealed that the compositions of phytoplankton communities, collected from the 21 sampling sites in the riverine wetlands of reservoir stretch, flow-reduced stretch, and natural stretch, were dissimilar. The communities of phytoplankton were clustered into three groups. The co-occurrence network analysis indicated that the interspecific relationship structures of phytoplankton communities of each group were different. The indicator species Chlamydomonas ovalis, Synedra acus, and Chlamydomonas globosa, belonged to the Reservoir Wetlands Group, Diatoma vulgare, Fragilaria ca pucina, and Meridion circulare belonged to the Flow-reduced Wetlands Group, and Ceratoneis arcus and Treubaria crassispina belonged to the Natural Wetlands Group. The functional group L0 was the absolute dominant group in all three groups of the riverine wetlands, but a discrepancy was that the proportions of functional group X2 and functional group C in the Reservoir Wetlands Group were remarkably higher, while the proportion of functional group MP in the Flow-reduced Wetlands Group was noticeably higher. By assessing the status of the phytoplankton community composition and the functional group structure, we concluded that current velocity and water depth were crucial influencing factors, and the functional group structure based on the classification of livable water could be applied as a good indication for demonstrating phytoplankton community succession.